Anomalous kinetics of diffusion-controlled defect recombination in irradiated oxide crystals - Kuzovkov, V.N.; Kotomin, E.A.; Popov, A.I. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Anomalous kinetics of diffusion-controlled defect recombination in irradiated oxide crystals